Modelling awareness of diabetes mellitus : case study at two public health centres - Humaira’, Abdul Latif (2019)
Diabetes is an increasingly growing health concern in Malaysia and the increase in the number of diabetics is worrying. Diabetes is a chronic disease in which the human body is unable to produce or utilize insulin. Insulin is a type of hormone needed to convert sugar, starches and other food into energy needed for daily life. The true cause of diabetes is still unknown, though genetics and the environment play an important role. Every year, the Ministry of Health launches a campaign to create awareness about the effects of diabetes. However, the prevalence of diabetes in Malaysia, especially Type 2, has increased to the epidemic. Therefore, this study proposes a conceptual model to study factors that may create awareness among the public in order to avoid the disease. This model was tested using an exploration approach through statistical modelling techniques to validate the hypothesised model which involved latent constructs such as knowledge about diabetes, attitude towards the disease, the environment surrounding it, symptoms and awareness of diabetes itself. A total of ten hypotheses were put forward to examine the relationships between the five constructs in the hypothesised model. A cross-sectional survey was used in this study, and it was carried out at two health clinics of the Ministry of Health Malaysia (MoH) in Pahang. A total of 441 adults were involved while attending the outpatient department at Klinik Kesihatan Paya Besar and Klinik Kesihatan Padang Rumbia. The sampling used convenience sampling that was conducted from 1 September 2015 to 15 October 2015. Partial Least Squares-Structural Equation Modelling (PLS-SEM) technique was used to test the hypothesised model and examine the relationships between the constructs in the Diabetes Mellitus Awareness Model (DMAM). The results showed that the knowledge had a significant impact on the environment, attitude, and awareness. Meanwhile, environment significantly influenced the attitude whereas attitude had a significant relationship with awareness. However, the findings also indicated that the environment had no significant relationship with awareness and the environment did not have any significant effect on symptoms of diabetes mellitus. The causal relationship between attitude with symptoms, and the relationship between symptom and awareness were also not significant. In general, this study concludes with the relationships that are both statistically significant and insignificant, therefore, due care should be paid and given a due attention by the authorities in order to jumpstart in raising awareness of diabetes mellitus among public. Although the sampling in limited to population in Kuantan Pahang only, but the results of the study could be beneficial for most relevant authorities especially the Ministry of Healths to take further actions for improving the level of awareness among Malaysians.